(untitled) (Linguist, 2021)
The development This research aims to identify the meaning of fallacy using the measurement of intention. In fact, fallacy ,as presented by the majority of the linguistic and terminological Arabic dictionaries, is not an inattentively made mistake that the speaker commits in his speech but rather an intentional wrongdoing by which he manipulates the listener so that he falls into the trap of misconception and judgments that doesn’t fit the validity of the things in reality. The research starts with admitting the strong relation that exists between the concepts of “intention” and “fallacy” in our Arab heritage by tracing the most important definitions that were given to the concept of fallacy. And it basically focuses on the main lexical definitions that the Arab philosophical schools contributed to creating in this field. All with taking into consideration that fallacy –as it will be shown in the research– is basically a logical concept created by the Arabic explanation of Aristotle’s Organon, before its transition into other rhetorical, argumentative fields later. The research ends with representing the importance of intentionality in establishing the concept of fallacy, and considers it, in the ancient Arab perspective, an original norm in attributing the judgment of the value; judge the speech as fallacious or not. And then the research tends to make a comparison between the Arab heritage blog and the western theory prevailing nowadays. And it heads mainly to what some contemporary Anglophonic pragma-dialectical approach suggests: to absent the concept of intentionality and to weaken it in the rhetorical calculation of fallacies.